Spontaneous Coronary Artery Dissection following Topical Hormone Replacement Therapy - Alexander L. Pan; David Fergusson; Robert Hong; Ramy A. Badawi (Case Reports in Cardiology)
Spontaneous coronary artery dissection is a rare condition, usually presenting as an acute coronary syndrome, and is often seen in states associated with high systemic estrogen levels such as pregnancy or oral contraceptive use. While topical hormonal replacement therapy may result in increased estrogen levels similar to those documented with oral contraceptive use, there are no reported cases of spontaneous coronary dissection with topical hormonal replacement therapy. We describe a 53-year-old female who developed two spontaneous coronary dissections while on topical hormonal replacement therapy. The patient had no other risk factors for coronary dissection. After withdrawal from topical hormonal therapy, our patient has done well and has not had recurrent coronary artery dissections over a one-year follow-up period. The potential contributory role of topical hormonal therapy as a cause of spontaneous coronary dissection should be recognized.